2020
DOI: 10.1002/int.22219
|View full text |Cite
|
Sign up to set email alerts
|

An epsilon‐constraint method for fully fuzzy multiobjective linear programming

Abstract: Linear ranking functions are often used to transform fuzzy multiobjective linear programming (MOLP) problems into crisp ones. The crisp MOLP problems are then solved by using classical methods (eg, weighted sum, epsilon‐constraint, etc), or fuzzy ones based on Bellman and Zadeh's decision‐making model. In this paper, we show that this transformation does not guarantee Pareto optimal fuzzy solutions for the original fuzzy problems. By using lexicographic ranking criteria, we propose a fuzzy epsilon‐constraint m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 43 publications
(117 reference statements)
1
18
0
Order By: Relevance
“… -constraint is a broadly applied method to get the exact solutions for multi-objective problems [57] . Plenty of successful applications have been reported to solve various problems for this method [58] .…”
Section: Solution Methodsmentioning
confidence: 99%
“… -constraint is a broadly applied method to get the exact solutions for multi-objective problems [57] . Plenty of successful applications have been reported to solve various problems for this method [58] .…”
Section: Solution Methodsmentioning
confidence: 99%
“…Pérez-Cañedo et al [15] showed that the transformation of FFMOLP problems into crisp multi-objective linear programming problems by means of linear ranking functions does not guarantee Pareto optimal fuzzy solutions. Thus, taking as a starting point the lexicographic method for fully fuzzy single-objective linear programming presented in Section 2.3.6, in [15], the authors extended the classical definitions of dominance and Pareto optimality to the fuzzy case using lexicographic ranking criteria, and proposed a fuzzy epsilon-constraint method that guarantees Pareto optimal fuzzy solutions. In what follows, we briefly present their approach only considering the minimization case.…”
Section: Fuzzy Epsilon-constraint Methodsmentioning
confidence: 99%
“…Despite being widely used, linear ranking functions have little discriminative capabilities, as they may map different FNs into the same real number, which, in turn, may yield unreasonable results [14]. Lexicographic ranking criteria can overcome this issue by defining multiple comparison indices arranged in a hierarchical fashion [15]. This fact has motivated the development of lexicographic methods for FLP.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional optimization algorithms are generally aimed at structural problems, most of which fall into the category of convex optimization [9]. The essence of the algorithm is to transform multiple objective functions into a single objective function based on some rules and then solve the MOP by a single-objective optimization method [10,11]. Although the traditional optimization algorithm has a fast convergence speed and a clear termination criterion, it can only find one of the Pareto solution sets of the optimization problem at a time, and the solution results are strongly dependent on the initial values.…”
Section: Introductionmentioning
confidence: 99%